TikTok as Media of Learning English: Experimental research on the third class of senior high - Imam nur Aziz; Rahmanda Hemas Sabella (JEET, Journal of English Education and Technology, 2021)
This article is about using TikTok as media of teaching elementary speaking in pandemic era. There are various strategies to teach speaking during the COVID-19 epidemic, including social media revolutionizing educational contexts. TikTok became a popular source of information for learning and knowing about popular culture and other issues, and even news. true-experimental design was used to examine the experiment and control group. The results of statistic analysis, hypothesis, and the pre-test post-test were included in the data. It shows that both groups was 79.00<108.00 for the experimental group and 84.50<85.00 for the control group, it was concluded that from the post-test of both groups was 85.00<108.00, because after giving the treatment by using TikTok or no, showed the significant difference result between both groups. An independent sample test showed the score of Sig.(2-tailed) was 0.000 lower than 0.05, which means the Alternative Hypothesis (Ha) was accepted, so using TikTok application in teaching speaking can encourage the fluency of students' elementary speaking ability.